2021
DOI: 10.2147/nss.s299382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obstructive Sleep Apnea Among Saudi Pilots

Abstract: Purpose To evaluate the presence of obstructive sleep apnea (OSA), using home sleep testing in pilots and first officers in Saudi-based airlines. This will allow for proper diagnosis and management of OSA in that group which can help in minimizing any possible aviation accidents related to sleep disturbances secondary to OSA. Materials and Methods This is a cross-sectional study conducted through Saudi-based aviation among pilots and first officers who were in service, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Mild excessive daytime sleepiness was detected among 12.5% of our population, 8.3% was moderate, and the rest (6.1%) was severe. Like the study in Jeddah, Saudi Arabia, excessive daytime sleepiness was reported by 23.1% of the Saudi pilots [12]. The author explained that Saudi airline pilots and first officers are prone to this kind of disorder due to the airline crews are required to cope with very early and very late flights, traversing different time zones, and sleep deprivation leading to fatigue and increasing physical and mental health disorders.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mild excessive daytime sleepiness was detected among 12.5% of our population, 8.3% was moderate, and the rest (6.1%) was severe. Like the study in Jeddah, Saudi Arabia, excessive daytime sleepiness was reported by 23.1% of the Saudi pilots [12]. The author explained that Saudi airline pilots and first officers are prone to this kind of disorder due to the airline crews are required to cope with very early and very late flights, traversing different time zones, and sleep deprivation leading to fatigue and increasing physical and mental health disorders.…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with our findings, in a study conducted in Riyadh [ 11 ] using the Berlin Questionnaire (BQ), the prevalence of OSA symptoms was 21.7%, wherein the prevalence was higher in males (78.3%) than in females (21%). However, in Jeddah, Saudi Arabia, using a similar questionnaire, [ 12 ] the author discovers that Saudi pilots had a greater prevalence of OSA, with prevalence rates of 69% according to home sleep testing, majority of which had mild OSA (64%), and 5% had moderate and severe OSA (2.5% each).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies highlighted the effect of weight reduction on OSA; 10% reduction in body weight can decrease AHI by 26% 22 . Other studies estimated a reduction in AHI by 47% and 61% could be achieved by 9% and 17% body weight reduction 41,42 Secondly, OSA is prevalent among drivers and pilots and its effects may extend beyond medical comorbidities to increase the risk of car tra c accidents 43,44 . Hence, we recommend OSA screening for vital and related jobs such as drivers and pilots Furthermore, this study underlines the need for raising awareness of OSA among the public and, in advance, the medical personnel.…”
Section: The Variablementioning
confidence: 99%
“…8 However, only a few Middle Eastern research have calculated the prevalence of sleep apnea. 9,10,11 Prevalence of OSA symptoms among the adult population in Saudi Arabia, the median age of the respondents was 30 years with 26.9% of people having OSA symptoms. Mild, moderate, and severe excessive daytime sleepiness were detected in 12.5%, 8.3%, and 6.1%, respectively, according to the severity of OSA symptoms.…”
Section: Introductionmentioning
confidence: 99%